2021
DOI: 10.1002/anie.202104164
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled Cage for Wide‐Scope Chiral Recognition in Water

Abstract: Herein, we report the self-assembly of an anionic homochiral octahedral cage by condensing six Ga 3+ cations and four trisacylhydrazone ligands.T he robust nature of the hydrazone bond renders the cage stable in water,where it can take advantage of the hydrophobic effect for host-guest recognition. In addition to the internal binding site,n amely, the inner cavity,the octahedral cage possesses four "windows", each of which represents an external binding site allowing peripheral complexation. These internal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 87 publications
1
34
0
Order By: Relevance
“…S19, ESI † ). 50 Three sets of signals belong to free S2 (black), one porphyrin adduct S2⊃G (green), and two porphyrin adducts S2⊃G 2 (yellow), respectively, with continuous charge states from 11+ to 21+, in Fig. 8b , consistent with the TWIM-MS spectrum ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…S19, ESI † ). 50 Three sets of signals belong to free S2 (black), one porphyrin adduct S2⊃G (green), and two porphyrin adducts S2⊃G 2 (yellow), respectively, with continuous charge states from 11+ to 21+, in Fig. 8b , consistent with the TWIM-MS spectrum ( Fig.…”
Section: Resultssupporting
confidence: 71%
“…Although calibration curves have been constructed for several hosts with a variety of chiral analytes, [25,28,54,55,66] they are rarely used for the determination of ee values and the absolute configuration of real samples. We have demonstrated that amide naphthotubes can be used for chirality analysis of the products from the catalytic asymmetric epoxidation of styrene and asymmetric hydrogenation of acetophenone.…”
Section: Applications Of Chiroptical Sensingmentioning
confidence: 99%
“…Therefore, they can be used for chirality analysis. Li and co‐workers [28] reported an anionic homochiral octahedral cage ( 9 , Figure 6a) self‐assembled from six Ga 3+ cations and four trisacylhydrazone ligands in water. The cage is a racemic mixture consisting of two homochiral enantiomers.…”
Section: Chiroptical Sensing With Self‐assembled Hostsmentioning
confidence: 99%
“…Since the first serendipitous isolation of a self-assembled tetrahedral coordination cage, the development of discrete three-dimensional (3D) coordination cages, especially water-soluble molecular cages comprising accessible cavities, has attracted a great deal of research attention. Such molecular cages adopt different geometries and include accessible hydrophobic inner spaces; indeed, these species have found widespread use in the selective encapsulation, separation, and release of a variety of guest molecules, as well as in the promotion of chemical reactions in the aqueous phase. The design and development of new systems that can distinguish between structurally similar compounds would provide new applications for self-assembled tetrahedral coordination cages, especially in the context of the separation of isomeric molecules.…”
Section: Introductionmentioning
confidence: 99%